2015
DOI: 10.1364/oe.23.028471
|View full text |Cite
|
Sign up to set email alerts
|

Robustness and spatial multiplexing via diffractal architectures

Abstract: When plane waves diffract through fractal-patterned apertures, the resulting far-field profiles or diffractals also exhibit iterated, self-similar features. Here we show that this specific architecture enables robust signal transmission and spatial multiplexing: arbitrary parts of a diffractal contain sufficient information to recreate the entire original sparse signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The aperture-selected fields are reconstructed by a second, Fourier transform lens. 18 What is powerful about diffractal propagation is that the central portion of the diffractal is not needed to reconstruct a kernel code and that the original pattern is mostly reconstructed optically.…”
Section: Introductionmentioning
confidence: 99%
“…The aperture-selected fields are reconstructed by a second, Fourier transform lens. 18 What is powerful about diffractal propagation is that the central portion of the diffractal is not needed to reconstruct a kernel code and that the original pattern is mostly reconstructed optically.…”
Section: Introductionmentioning
confidence: 99%
“…The unique property of diffractal redundancy enables misaligned or non-coaxial roaming transceiver 30,31 . The proposed DSDM system involves: multiplexing (where the transmitted data is a fractal from kernel data), diffraction encoding (when the beam propagates to the receiver), and demultiplexing (which is hybrid system, composed of an optical receiver and a software reconstruction) [Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1]. The most closely-related work related to DSDM in FSO is by M. Moocarme et al, where diffractal multiplexing is demonstrated with a 4-F lens system using on/off keying (OOK) 30 . In the focal plane or far field, a portion of the Fourier transform of the transmitted fractal pattern contains sufficient information to recreate the entire original (sparse) signal 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…1. The unique properties of diffractal redundancy enable the simultaneous transmission of multiple independent bit streams; 36,37 in the far field, arbitrary parts of a diffractal contain sufficient information to recreate the entire original (sparse) signal. 38,39 Transmitted beams with higher fractal orders achieve higher reconstruction accuracy [see right column of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1]; in prior work, this result has been demonstrated experimentally with a 4-F system. 36 Since DSDM does not rely on wavelength or polarization, it could be used with WDM and PDM techniques to further improve system capacity. Additionally, DSDM may be used to improve data transmission capacity in adverse environments in a manner analogous to other FSO techniques in which different parts of a signal are referenced to reduce receiver error.…”
Section: Introductionmentioning
confidence: 99%